2015
DOI: 10.1016/j.nlm.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of N-methyl-D-aspartate receptors to attention and episodic spatial memory during senescence

Abstract: A decrease in N-methyl-D-aspartate receptor (NMDAR) function is associated with age-related cognitive impairments. However, NMDAR antagonists are prescribed for cognitive decline associated with age-related neurodegenerative disease, raising questions as to the role of NMDAR activity in cognitive function during aging. The current studies examined effects of NMDAR blockade on cognitive task that are sensitive to aging. Young and middle-age rats were trained on the five-choice serial reaction time task (5-CSRTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 86 publications
1
25
0
Order By: Relevance
“…We observed that rats collided with the paddle within the treadmill less frequently after 10 mg/kg ketamine than at baseline, suggesting that ketamine induced an increase in attention during the walking task. This supports the idea that gamma power and attention are correlated [ 99 ], even when induced by ketamine, and is consistent with a recent study showing that ketamine increases attention in young rodents [ 100 ].…”
Section: Discussionsupporting
confidence: 92%
“…We observed that rats collided with the paddle within the treadmill less frequently after 10 mg/kg ketamine than at baseline, suggesting that ketamine induced an increase in attention during the walking task. This supports the idea that gamma power and attention are correlated [ 99 ], even when induced by ketamine, and is consistent with a recent study showing that ketamine increases attention in young rodents [ 100 ].…”
Section: Discussionsupporting
confidence: 92%
“…Methods for training animals on the water maze task have been adapted from Guidi et al (2015). Animals were trained in a black tank, 1.7 m in diameter, positioned in a well-lit room containing (when appropriate) an assortment of 2-and 3-dimensional cues.…”
Section: Water Maze Testing For Memory Apparatusmentioning
confidence: 99%
“…Three days following the initial cue discrimination training, animals were trained on a modified version of the DMTP task, which is sensitive to aging (Foster, 2012;Guidi et al, 2015). The platform was lowered to just beneath the water surface and animals were trained to find a hidden platform.…”
Section: Delayed-matching-to-place (Dmtp) Taskmentioning
confidence: 99%
“…NMDA receptors play an important role in learning and memory, and are critical for spatial memory (Morris et al, 1986 ; Collingridge, 1987 ; Mondadori et al, 1989 ; Morris, 1989 ; Mondadori and Weiskrantz, 1993 ; Lisman et al, 1998 ; Martin et al, 2000 ; Foster, 2012 ; Guidi et al, 2015b ); NMDA receptor-mediated synaptic plasticity and its hypofunction is thought to play a vital role in age-associated cognitive impairments (Foster and Norris, 1997 ; Foster, 2012 ; Kumar and Foster, 2013 ). Advanced age is associated with a decrease in subunit expression and a decline in NMDA receptor function.…”
Section: Nmda Receptor Hypofunction and Its Influence On Cognitive Pementioning
confidence: 99%